2000
DOI: 10.1177/135245850000600304
|View full text |Cite
|
Sign up to set email alerts
|

Lesion pattern in patients with multiple sclerosis and depression

Abstract: To assess if a specific lesion pattern or changes of the basal limbic system as seen in primary depression and depression associated with neurodegenerative disorders might be identified in depressive multiple sclerosis (MS) patients, we submitted 78 MS patients to a MRI examination consisting of a quantitative measurement of lesions and of hyperintense signals from the pontomesencephalic midline (raphe). Furthermore relaxometry of the pontomesencephalic midline, a transcranial ultrasound examination rating its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(28 citation statements)
references
References 58 publications
(29 reference statements)
3
21
1
3
Order By: Relevance
“…There is, however, no clear consensus about what the neurobiological differences between depressed MS patients and non-depressed MS patients might be. While some comparative studies using MRI have found no differences in lesion distribution between depressed and non-depressed MS patients [38], other studies have suggested an increase in lesions in specific brain areas among depressed MS patients, including the right temporal lobe [41], the left hemisphere suprasylvian region [42], and the superior frontal or parietal regions. [43] Similarly, little is known about the specific nature of the interactions between the neuroimmunology of MS and depressive disorders.…”
Section: Neurobiology Of Depression In Msmentioning
confidence: 97%
“…There is, however, no clear consensus about what the neurobiological differences between depressed MS patients and non-depressed MS patients might be. While some comparative studies using MRI have found no differences in lesion distribution between depressed and non-depressed MS patients [38], other studies have suggested an increase in lesions in specific brain areas among depressed MS patients, including the right temporal lobe [41], the left hemisphere suprasylvian region [42], and the superior frontal or parietal regions. [43] Similarly, little is known about the specific nature of the interactions between the neuroimmunology of MS and depressive disorders.…”
Section: Neurobiology Of Depression In Msmentioning
confidence: 97%
“…The etiological mechanism of the depression in MS is still unclear, but there are some reports that indicate that cortical-subcortical disconnection in the projections areas of the limbic system may be responsible [20]. Correlation with lesion load in the temporal regions has also been suggested [21].…”
Section: Discussionmentioning
confidence: 99%
“…Most published studies found similar levels of anxiety among MS patients and normal controls, and no correlation between the symptoms of anxiety and either brain MRI abnormalities or clinical variables [20] and [25]. However, Riether emphasizes that anxiety is frequently overlooked in MS patients, especially that induced by treatment with corticosteroids [26].…”
Section: Discussionmentioning
confidence: 99%
“…Although some investigators have failed to demonstrate an association between the presence of MRI abnormalities and affective symptoms, others have found association between depression and temporal lobe involvement 7,25 lesions in the right parietal region 26 , the left frontal lobe 27 , the left arcuate fasciculus 8,9 or the total lesion load 28 . Additionally, a disconnection between subcortical and cortical areas connected to the limbic system has been proposed 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Although affective symptoms in multiple sclerosis (MS) have been noticed since its clinical characterization by Charcot 1 only in the last two decades more detailed studies dealing with their prevalence, causality, profile and treatment have been carried out [2][3][4][5][6][7][8][9] . Depressive symptoms of sufficient severity and duration to warrant a diagnosis of major depression affect 25 to 50% of MS patients during the course of disease 2,3 .…”
mentioning
confidence: 99%